The nature theme in the works for children and about children by Yevgen Gutsalo (Literatures of the World: Poetics, Mentality and Spirituality, 2017)
The works of YevhenHutsalo for and about children are analyzed in the article in the aspect of peculiarity of descovering the theme of nature. The attention is accentuated to the dependence of forms of nature representation from the age qualification of the reader, author’s ability to synchronize objective information about environment with individual emotional loading of the narrator. Contemplative manner of writing, synthesis of realistic precision and verbal and artistic figurativeness, appeal to markers of Ukrainian culture, ability to dialogue with the reader without embarrassment, simply, subtly feeling the smallest movements of the soul, characterize the prose of YevhenHutsalo for and about children.
Keywords: literature for children; literature about children; author; reader; character; prose; nature; theme